Output Persistence in Portugal - Caleiro, António (2013)
The measurement of output persistence in Portugal is the main goal of this paper. By the use of a non-parametric methodology, it is shown that the level of output in Portugal exhibits a relatively high degree of persistence. This result is essential from a (contractionary/expansionary) policy point of view as the magnitude and duration of policy effects depend upon the level of persistence in output.